2013
DOI: 10.1111/jph.12187
|View full text |Cite
|
Sign up to set email alerts
|

Fig Viruses in Mainland Spain

Abstract: A survey of fig viruses was conducted from 2010 to 2012 on individual fig trees from outdoor gardens showing different symptoms associated with fig mosaic disease. A total of 30 fig leaf samples were collected from eight different provinces of mainland Spain and tested by reverse transcription polymerase chain reaction (RT‐PCR) to assess the presence of fig mosaic virus (FMV), fig leaf mottle‐associated virus 1 (FLMaV‐1), fig leaf mottle‐associated virus 2 (FLMaV‐2), fig mild mottle‐associated virus (FMMaV), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…These findings are consistent with those of Ref. [ 43 ], who stated that sequencing analyses revealed that FMV and FLMaV-1 Spanish isolates shared 89–93% identity with other Mediterranean isolates of the same viruses reported in the GenBank database. On the other hand, Ref.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with those of Ref. [ 43 ], who stated that sequencing analyses revealed that FMV and FLMaV-1 Spanish isolates shared 89–93% identity with other Mediterranean isolates of the same viruses reported in the GenBank database. On the other hand, Ref.…”
Section: Discussionsupporting
confidence: 93%
“…Both the percentage occurrence and distribution of FFkaV were similar to that of FMV, and the high percentage occurrence (79.3%) in symptomatic samples and low incidence (23.5%) in asymptomatic samples indicates an association between these viruses. However, the percentage occurrence of FFkaV in diseased samples was significantly lower in previous studies (Alfaro-Fernández et al 2014;El Air et al 2015). More research is therefore needed to investigate the relationship between FFkaV and FMD.…”
Section: Resultsmentioning
confidence: 56%